DIET QUALITY IS ASSOCIATED WITH FRAILTY IN THE PHYSICIAN'S HEALTH STUDY. (11th November 2018) - Ward, R; Orkaby, A; Hshieh, T; Driver, J; Gaziano, J; Djousse, L
Abstract: Increasing evidence suggests that healthier dietary patterns may be inversely associated with frailty, although whether this relationship holds across various diet indices is unknown. We investigated whether dietary patterns are associated with frailty among male physicians using 3 dietary assessments: the Alternate Healthy Eating Index (aHEI), Mediterranean diet (MED), and Dietary Approaches to Stop Hypertension (DASH). Our analysis included 12, 240 men aged ≥60 years who provided data to determine frailty status and dietary habits. A cumulative deficit frailty index (FI) was calculated using 33 variables encompassing domains of comorbidity, functional status, mood, general health, social isolation, and change in weight. FI identified 36.6% of physicians as robust, 43.3% as pre-frail, and 20.1% as frail. Multinomial logistic regression models were adjusted for age, smoking status, aspirin and beta-carotene randomization, marital status, employment, and energy intake. Compared to the lowest quintiles of aHEI, MED, and DASH, those in the highest quintiles had a decreased odds of frailty [OR (95% CI) for aHEI: 0.53 (0.41, 0.67), MED: 0.42 (0.35, 0.51), and DASH: 0.45 (0.36, 0.56)] and pre-frailty [aHEI: 0.73 (0.62, 0.87), MED: 0.68 (0.59, 0.78), and DASH: 0.63 (0.54, 0.74)]. Restricted cubic splines showed a linear dose-response relationship of higher scores from each diet assessment with decreased odds of pre-frailty and frailty. Our findings confirm and inverse dose-response relationship of 3 different diet assessments with pre-frailty and frailty and suggest that healthier diet may be a potentially modifiable risk factor for frailty.